Faire face au contretemps pour faire son temps - Étienne Guillaud (Temporalités, 2017)
Nautical activities (sailing, surfing, kitesurfing…) are frequently conceived by sea resort municipalities as products for the tourist industry and therefore associated with vacation time. But they are also working time for those who are in charge. Nautical sports instructors are forced to work on the off-beat. They must integrate temporalities - school holidays, public holidays or week-ends - which are different from the ordinary working world. That is sometimes problematic, especially when conciliating work and family life.This paper focuses on the way sports teachers experience working on the off-beat, and how they perceive the situation. It will try to identify and to characterize the resources and strategies used for dealing with the various effects and consequences of working on the off-beat. The results presented are based on fieldwork with interviews and observations carried out on the coast of the Pays-de-la-Loire Region.